Prevention and control of intestinal parasitic infections : report of a WHO Expert Committee, meeting held in Geneva from 3 to 7 March 1986 - WHO Expert Committee on Prevention and Control of Intestinal Parasitic Infections; World Health Organization (Geneva : World Health Organization, 1987)
Outlines new approaches to the prevention and control of intestinal parasitic infections made possible by the recent discovery of safe and effective therapeutic drugs, the improvement and simplification of diagnostic procedures, and advances in the understanding of parasite population biology. Newly available information on the economic and social impact of these infections is used to illustrate the necessity, as well as the feasibility, of bringing these infections under control. In view of the striking variations in the biology of different intestinal parasites and in the form and severity of the diseases they cause, the book opens with individual profiles for each of the main helminthic and protozoan infections of public health importance. A second section examines the costs arising from failure to control intestinal parasitic infections. Effects on nutrition, growth and development, on work and productivity, and on medical care costs are considered together with example of national expenditures on the treatment of selected infections. Of particular practical value is a section outlining strategies for prevention and control. Readers are informed of the different approaches required for the major helminthic and protozoan infections, the approaches most appropriate for reaching short- and long-term objectives, and the factors that should be considered when evaluating priorities, costs and benefits. Additional information covers suitable methods and tools for monitoring and surveillance, data management, diagnosis, and chemotherapy.
1. Introduction -- 2. Public health significance of intestinal parasitic infections -- 3. The cost of not having a control programme -- 4. Prevention and control strategies -- 5. National programmes -- 6. Programme support -- 7. Conclusions -- 8. Recommendations -- Acknowledgement -- References
Keywords: Intestinal Diseases, Parasitic; Parasitic Diseases and their Control